Light-sensitive ceramic tile with combined dry particle and dazzling diamond effect and preparation method of light-sensitive ceramic tile
By using specific combinations of dry particles, including ceramic dry particles and zirconium sand dry particles, and adjusting their ratio so that transparent glass balls and mineral crystals are formed after firing, the glaze problem caused by dry particles in the existing ceramic tile process is solved, and the good crystal feeling and diamond-shaking effect of ceramic tile is achieved.
Patent Information
- Application Number
- CN202411821064.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
In the existing ceramic tile process, the incorporation of dry particles causes small pinholes to easily produce on the glaze surface, affecting stain resistance; the incorporation of dry particles into the glaze makes the glaze not easy to stir evenly, affecting the effect of drilling; high-temperature corrosive erosion of dry particles, resulting in unsatisfactory drilling effect.
A specific combination of dry particles, including ceramic dry particles and zirconium sand dry particles, is used to adjust the ratio of each component in the dry particles, so that transparent glass spheres and mineral crystals are formed after firing, and the high refractive index characteristics of the crystal are used to form a three-dimensional light wave body under light reflection, achieving visual effects at different angles.
It improves the crystalline feeling and transparency of ceramic tiles, and has a diamond-shaking effect, a flat glaze and good anti-fouling effect.
Smart Images

Figure CN119613154A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic tiles, and in particular relates to a light-sensitive ceramic tile with combined dry particles and dazzling diamond effect and a preparation method thereof. Background Art
[0002] With the instability of the international situation in recent years, which has affected the slow economic growth, the purchasing power of the consumer group has also tended to decline. All walks of life are also facing huge challenges, especially the ceramic industry, which is under tremendous competitive pressure and internal friction and involution are expanding. Modern consumers are more concerned about the actual quality of the products. Moreover, as an important part of decoration, the good quality of ceramics directly affects the effect of decoration.
[0003] At present, bright-faced tiles still occupy the majority of sales, but it has been difficult for related products to have more technological breakthroughs. The existing bright-faced tile processes include polishing glaze, dry-grain polishing, starry sky glaze, diamond glaze, marble and other few processes; the starry sky glaze and diamond glaze processes on the market basically adopt the method of adding dry grains into the polishing glaze, and then glazing on the brick surface and firing and polishing. This method has the problem that some of the added dry grains will penetrate the glaze surface after polishing, resulting in the glaze surface effect easily producing small pinholes, thus affecting the stain resistance. The addition of dry grains into the polishing glaze during production makes it difficult to stir the glaze evenly and the glaze is easy to stratify and precipitate. The dry grains in the glaze return tank during the glazing process are easy to settle in it, affecting the quality of the glazing. Because the glazing process is easy to evenly distribute the brick surface, the corresponding distribution of the dazzling diamond effect is not easy to change flexibly; at the same time, the proportion of dry grains added will affect the performance of the glaze, resulting in the dazzling diamond effect being limited by the technological performance of the glaze; when dry grains are added into the polishing glaze, the high-temperature corrosiveness of the polishing glaze itself will corrode the added dry grains, resulting in an unsatisfactory dazzling diamond effect. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the prior art. This invention provides a combination of dry particles, and then by studying the dry particle formula and process means, the proportion of each component in the dry particles is adjusted so that the dry particles include transparent glass balls formed in a molten state after firing, and also include unmelted mineral crystals. The high refractive index characteristics of crystal minerals are used to form a three-dimensional light wave body under the reflection of light, thereby forming different visual effects at different angles. The specific process is powder making, pressing blanks, and after the blanks are dried, glaze is applied to the brick surface, inkjet printing is performed by an inkjet machine, and glue is sprayed after inkjet printing. The combined dry particles are applied by a dry particle machine at the glue spraying position, and then the glaze is applied on it, and then the finished product is obtained by firing, polishing and grinding. In this method, the combined dry particles and the glaze are applied separately, which does not affect each other's own performance, and the high temperature corrosiveness of the glaze will also reduce the erosion of the combined dry particles. The ceramic tile of the present invention has a good crystal feel and transparency, and at the same time has a dazzling diamond effect.
[0005] Based on this, the first aspect of the present invention provides a combined dry particle, including ceramic dry particles and zircon sand dry particles; the raw materials for preparing the above-mentioned ceramic dry particles include, by weight: 2-7 parts of albite, 1-4 parts of dolomite, 15-21 parts of calcite, 9-13 parts of potassium carbonate, 5-10 parts of aluminum oxide, 45-55 parts of quartz powder, 0.5-1.5 parts of barium carbonate, and 6-10 parts of zinc oxide; the above-mentioned zircon sand dry particles are obtained by crushing zircon; the mass ratio of the above-mentioned ceramic dry particles to the above-mentioned zircon sand dry particles is (5-9): (1-5).
[0006] The present invention utilizes the characteristics of zircon's high melting point (2190°C-2420°C) and high refractive index (1.93-2.01) of the original ore, and uses it as a component of the combined dry particles, which can present a bright sparkle effect / dazzling diamond effect after being fired at 1200°C-1220°C in the tile glaze. However, in general, the glaze layer formed by the surface glaze needs a certain degree of transparency to better show the printing layer below, so the composition of the glaze needs to form more glass phases, that is, the mass percentage (content) of sodium oxide will be greatly increased to form a glass phase, and the mass percentage of potassium oxide will be reduced, but the above operation is bound to increase the high-temperature corrosiveness of the glaze, and then will corrode the surface of the above-mentioned zircon sand dry particles, affecting its refractive index and ultimately affecting its visible sparkle (i.e., bright sparkle effect / dazzling diamond effect) presentation.
[0007] On this basis, the present invention proposes to use the combined dry particles obtained by mixing the above-mentioned ceramic dry particles with the above-mentioned zirconium sand dry particles in a specific composition, which can well solve the above-mentioned technical problems. Specifically, the present invention adopts a relatively low mass percentage of sodium oxide (0.2%-0.9%) and a relatively high mass percentage of potassium oxide (7.1%-10.4%) in the ceramic dry particles to reduce the high-temperature corrosiveness of the glaze, and simultaneously adopts a relatively high mass percentage of calcium oxide (9.7%-13.6%), a relatively high mass percentage of zinc oxide (6.8%-11.6%) and a relatively low mass percentage of aluminum oxide (7.1%-13.6%). The calcium oxide glaze has the characteristics of low viscosity at high temperature and high viscosity at low temperature. The high viscosity at low temperature can prevent the erosion of the zircon sand dry particles by the polishing glaze, and the high viscosity itself also has less erosion on the zircon sand dry particles. In the high temperature section of 1200°C-1220°C, the viscosity is low and it is easy to flow, and can be quickly spread on the surface of the zircon sand dry particles. The high temperature section is then the temperature of the rapid cooling section, and the calcium oxide glaze is formed after extreme cooling. The calcium oxide glaze has a strong glass texture and transparency, and can be covered on the surface of the zircon sand dry particles to better reflect the flash of the zircon sand dry particles. When converted into raw material selection, the present invention uses 45-55 parts of quartz powder and 5-10 parts of aluminum oxide as ridge materials to form a skeleton; 2-7 parts of albite are used to introduce aluminum oxide and silicon dioxide, and sodium oxide is introduced at the same time to reduce the surface tension of the glaze and control its high-temperature corrosiveness; 1-4 parts of dolomite are used to introduce magnesium oxide and calcium oxide, which are used to reduce the firing temperature and increase transparency while promoting the dissolution of quartz powder and the formation of mullite; 15-21 parts of calcite are used to introduce calcium oxide, the role of calcium oxide is to form glass with silicon dioxide, and calcium oxide can also improve the elasticity, hardness and glossiness of the glaze, and increase the high-temperature fluidity of the glaze; 9-13 parts of potassium carbonate are used to introduce potassium dioxide to play a role of flux; 0.5-1.5 parts of barium carbonate are used to introduce barium oxide to improve the hardness, wear resistance and chemical corrosion resistance of the glaze; 6-10 parts of zinc oxide (99 zinc oxide can be selected) are used to play a role of flux, reduce the expansion coefficient of the glaze, improve the thermal stability of the product, and at the same time increase the gloss of the glaze surface and improve the elasticity of the glaze.
[0008] During the firing process of the final ceramic tile, the ceramic dry particles will form a melt that covers the surface of the zircon sand dry particles, and at the same time adhere to the glaze layer, the printing layer and the polishing layer.
[0009] In some preferred implementations, the particle size distribution of the above zircon sand dry particles is: 70 mesh-140 mesh ≥ 75%, 140 mesh-200 mesh ≤ 23%, below 200 mesh ≤ 1.8%, above 70 mesh ≤ 0.2%. If the particle size is too large, it is easy to affect the glaze surface, and if the particle size is too small, it cannot present a dazzling diamond effect. Specifically, if the particle size is coarser than 70 mesh, the particles are easy to bulge the glaze surface, and when the particles stand up, gaps are easily formed at the bottom, affecting the quality of the glaze surface; if the particles are finer than 140 mesh, the particles are too fine and lack visual perception, so the number of particles in this part should not be too much, and can be used to fill the gaps between particles.
[0010] It should be noted that all “%” in the present invention refer to “mass percentage”, which is equivalent to “mass fraction” and “mass percentage content”.
[0011] In some preferred implementations, the particle size distribution of the ceramic dry particles is the same as that of the zircon sand dry particles. Maintaining the same particle size distribution makes it easier to evenly mix the ceramic dry particles with the zircon sand dry particles.
[0012] Among the raw materials of the above-mentioned ceramic dry particles, the mass percentage of K2O in the chemical composition of albite is greater than 10.0%; the mass percentage of CaO in the chemical composition of calcite is 50%-58%, the mass fraction of SiO2 in the chemical composition of quartz powder is greater than 98%, the chemical composition of dolomite is MgO: 19%-24%, CaO: 30%-35%, and the mass fraction of BaO in barium carbonate is greater than 70%. The main chemical components of the ceramic dry particles include, by mass percentage: SiO2: 54.6%-63.8%, Al2O3: 7.1%-13.6%, MgO: 0.5%-1.3%, CaO: 9.7%-13.6%, Na2O: 0.2%-0.9%, K2O: 7.1%-10.4%, BaO: 0.4%-1.4%, ZnO: 6.8%-11.6%, the mass percentage of Fe2O3+TiO2 is less than 0.2%, and the remainder is loss on ignition and impurities.
[0013] In the chemical composition of the above zircon sand dry particles, the mass fraction of ZrO2 is greater than 60%, the mass fraction of Fe2O3 is less than 0.8%, the mass fraction of TiO2 is less than 3.5%, the mass fraction of Al2O3 is less than 1.2%, and the mass fraction of SiO2 is less than 34%.
[0014] The second aspect of the present invention provides a method for preparing the above-mentioned combined dry particles, comprising the following steps: mixing the above-mentioned ceramic dry particles with the above-mentioned zircon sand dry particles to obtain the above-mentioned combined dry particles; the preparation process of the above-mentioned ceramic dry particles comprises the following steps: mixing the above-mentioned raw materials and then melting them, quenching with water to form frit particles, drying, and crushing. Since the combined dry particles are to be between the two glaze layers of the surface glaze and the polishing glaze, it is necessary to minimize the volatile components to avoid forming pinholes on the glaze surface. Therefore, in the preparation process of the above-mentioned combined dry particles, the raw materials are fully chemically reacted in a high-temperature molten state to reduce the generation of volatile components by chemical reactions again during the later firing process of the ceramic tiles.
[0015] The melting temperature is 1530°C-1570°C; and the drying is performed until the moisture content is less than 0.05%.
[0016] The third aspect of the present invention provides a dazzling diamond effect light-sensitive ceramic tile, which includes from bottom to top: a body layer, a glaze layer, a printing layer, a glue dry particle layer, and a glaze layer; the above-mentioned glue dry particle layer includes the above-mentioned combined dry particles. The product specifications of the ceramic package can be different specifications, including 600*600 mm, 800*800 mm, 600*1200 mm, 750*1500 mm, 800*1600 mm, 900*1800 mm, 800*2600 mm, 1200*1200 mm, 1200*2700 mm and other specifications.
[0017] In some preferred implementations, the above-mentioned glaze layer is formed by glaze, and the above-mentioned glaze includes, by weight: 8-12 parts of nepheline powder, 6-10 parts of potassium feldspar, 8-12 parts of A11 sodium feldspar, 13-17 parts of A10 sodium feldspar, 10-14 parts of A9 sodium feldspar, 8-12 parts of quartz, 7-11 parts of high white alumina, 10-14 parts of calcined kaolin, 0.5-2 parts of dolomite, 1-5 parts of burned talc, and 5-12 parts of zirconium silicate. The glaze layer is formed by a glaze containing the above-mentioned raw materials, and the corresponding chemical composition of the glaze includes: SiO2: 56.3%-57.5%, Al2O3: 22.2%-29.4%, MgO: 0.5%-2.3%, CaO: 1.1%-1.6%, Na2O: 4.7%-6.2%, K2O: 1.1%-1.7%, ZrO2: 3.1%-7.7%, ignition loss 1.3%-2.0%, and the remainder is impurities.
[0018] In some preferred implementations, the glaze layer is formed by glaze, which includes, by weight: 8-12 parts of A11 sodium feldspar, 13-17 parts of A10 sodium feldspar, 18-24 parts of A9 sodium feldspar, 4-8 parts of quartz powder, 4-8 parts of calcined kaolin, 13-17 parts of dolomite, 4-8 parts of burned talc, 1-5 parts of wollastonite, 4-8 parts of strontium carbonate, 0.5-3 parts of barium carbonate, 1.5-5.5 parts of zinc oxide, and 6-10 parts of ball clay. The glaze layer is formed by a glaze containing the above-mentioned raw materials, and the corresponding chemical composition of the glaze includes: SiO2: 43.9%-54.1%, Al2O3: 11.3%-16.8%, MgO: 4.3%-6.6%, CaO: 4.9%-7.7%, Na2O: 4.2%-5.8%, K2O: 0.26%-0.34%, SrO: 2.7%-5.6%, BaO: 0.4%-2.4%, ZnO: 1.5%-5.5%, ignition loss: 8.7%-12.3%, and the remainder is impurities.
[0019] The A9 sodium feldspar comprises, by mass percentage, SiO2: 72.30%, Al2O3: 16.63%, Fe2O3: 0.18%, TiO2: 0.03%, CaO: 0.57%, MgO: 0.36%, K2O: 0.39%, Na2O: 8.90%, and loss on ignition: 0.65%; the A10 sodium feldspar comprises, by mass percentage, SiO2: 72.78%, Al2O3: 16.65%, Fe2O3: 0.11%, T iO2: 0.06%, CaO: 0.54%, MgO: 0.17%, K2O: 0.11%, Na2O: 9.23%, loss on ignition 0.36%; the above-mentioned A11 albite includes, by mass percentage: SiO2: 73.18%, Al2O3: 16.46%, Fe2O3: 0.10%, TiO2: 0.07%, CaO: 0.55%, MgO: 0.17%, K2O: 0.18%, Na2O: 9.01%, loss on ignition 0.29%.
[0020] In the composition of the above-mentioned top glaze and polishing glaze, choosing different types of albite for mixed use can reduce the composition fluctuation caused by a single type of albite, thereby stabilizing the firing temperature.
[0021] In some preferred implementations, the raw materials of the green body layer include, by weight: 13-17 parts of white sand, 10-14 parts of ball clay, 2-6 parts of sodium stone powder, 26-32 parts of potassium sodium stone powder, 13-17 parts of kaolin, 3-7 parts of bentonite, 3-7 parts of talcum particles, 0-5 parts of rotten brick particles, 4-8 parts of raw clay, and 5-9 parts of diopside.
[0022] The fourth aspect of the present invention provides a method for preparing the above-mentioned dazzling diamond effect photosensitive ceramic tile, comprising the following steps: applying a surface glaze on the above-mentioned green body layer to form the above-mentioned surface glaze layer, then inkjet printing to form a printing layer, and printing colloidal ink on the pattern of the above-mentioned printing layer, then applying the above-mentioned combined dry particles, removing the above-mentioned combined dry particles that are not stuck (the non-sticky combined dry particles can be sucked away by an exhaust fan), then applying a polishing glaze to form the above-mentioned polishing glaze layer, and firing to obtain the dazzling diamond effect photosensitive ceramic tile.
[0023] The firing temperature is 1200°C-1220°C, and the firing time is 30min-60min. After the firing is completed, the ceramic tile with diamond effect is obtained by polishing, waxing and edge grinding.
[0024] Among them, an automatic dry granulator is used to apply combined dry granules. The dry granulator automatically applies combined dry granules according to the grayscale of the glue channel, and will not apply combined dry granules where there is no glue grayscale. This method of positioning the combined dry granules by dry method, piling them up at the texture and then forming a glaze layer can make the pattern more three-dimensional and natural, and not easy to be imitated and copied.
[0025] The beneficial effects of the present invention are as follows: the combined dry particles used in the present invention can make the ceramic tile produce a dazzling three-dimensional shining shape, and the pattern is more three-dimensional and natural; and the ceramic tile has a smooth glaze surface and a good anti-fouling effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The product photo of the dazzling diamond effect light-sensitive ceramic tile prepared in Example 1 is shown;
[0027] Figure 2 The product photo of the dazzling diamond effect light-sensitive ceramic tile prepared in Example 2 is shown;
[0028] Figure 3 The product photo of the dazzling diamond effect light-sensitive ceramic tile prepared in Example 3 is shown;
[0029] Figure 4 The product photo of the dazzling diamond effect light-sensitive ceramic tile prepared in Example 4 is shown;
[0030] Figure 5 Shown is a product photo of the ceramic tile prepared in Comparative Example 3;
[0031] Figure 6 Shown is a product photograph of the ceramic tile prepared in Comparative Example 4. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0033] Example 1
[0034] A diamond effect light-sensitive ceramic tile comprises, from bottom to top, a body layer, a glaze layer, a printing layer, a glue dry particle layer, and a polishing glaze layer.
[0035] The glue dry particle layer includes combined dry particles, and the combined dry particles include ceramic dry particles and zircon sand dry particles. Among them, the raw materials of the ceramic dry particles include by weight: 4 parts of albite, 2 parts of dolomite, 18 parts of calcite, 11 parts of potassium carbonate, 7 parts of aluminum oxide, 49 parts of quartz powder, 1 part of barium carbonate, and 8 parts of 99 zinc oxide. The preparation method of ceramic dry particles includes the following steps: the weighed raw materials are mixed by a mixer, and then added to the frit furnace through a screw feeder, and melted into a liquid melt at a high temperature of 1545°C. The melt flows out of the free fall body to the water guide trough below after it overflows the flow outlet, and the cooling water quenches the melt fluid while flowing to the water pool below. A collection basket is placed in the water pool. The melt fluid will be broken into frit particles after being quenched by cooling water, and the frit particles flowing out are collected in the collection basket. After the frit particles in the collection basket are full, they are hoisted to the drainage platform by an aerial crane. After the frit particles drain a part of the water, they enter the transfer bin for homogenization and further drainage. After a portion of water is drained from the transfer bin, the frit particles enter the drying kiln to dry the moisture to less than 0.05%. The dried frit particles are crushed into particles with a particle size distribution of 70 mesh-140 mesh ≥75%, 140 mesh-200 mesh ≤23%, below 200 mesh ≤1.8%, and above 70 mesh ≤0.2%, namely, ceramic dry particles. Among them, the preparation method of zircon sand dry particles includes the following steps: zircon (the mass fraction of ZrO2 is greater than 60%, the mass fraction of Fe2O3 is less than 0.8%, the mass fraction of TiO2 is less than 3.5%, the mass fraction of Al2O3 is less than 1.2%, and the mass fraction of SiO2 is less than 34%) is crushed into particles with a particle size distribution of 70 mesh-140 mesh ≥75%, 140 mesh-200 mesh ≤23%, below 200 mesh ≤1.8%, and above 70 mesh ≤0.2%, namely, zircon sand dry particles. Weigh 70 parts of ceramic dry particles and 30 parts of zircon sand dry particles, stir and mix them evenly to form combined dry particles.
[0036] The surface glaze layer is formed by the surface glaze, which includes, by weight: 10 parts of nepheline powder, 8 parts of potassium feldspar, 10 parts of A11 sodium feldspar, 15 parts of A10 sodium feldspar, 12 parts of A9 sodium feldspar, 10 parts of quartz, 9 parts of high white alumina, 12 parts of calcined kaolin, 1 part of dolomite, 3 parts of burned talc, and 10 parts of zirconium silicate. The chemical composition corresponding to the surface glaze includes: SiO2: 56.82%, Al2O3: 25.59%, MgO: 1.35%, CaO: 1.24%, Na2O: 5.23%, K2O: 1.40%, ZrO2: 6.34%, ignition loss 1.42%, and the remainder is impurities. The raw materials of the above glaze are mixed with 0.15 parts of sodium carboxymethyl cellulose, 0.35 parts of sodium tripolyphosphate and 40 parts of water, and added into a ball mill for ball grinding until the particle size meets the requirements. The qualified particle size requirements are: at least 100 mL of the material is pre-screened through a 100-mesh sieve, and then 100 mL of the sieved liquid is screened through a 325-mesh sieve, and the residue is weighed to be 0.3g-0.5g after drying; after the fineness meets the requirements, the ball is screened through a 120-mesh sieve to obtain the glaze, and then put into a slurry storage tank for use.
[0037] The glaze layer is formed by glaze, which includes by weight: 10 parts of A11 sodium feldspar, 15 parts of A10 sodium feldspar, 20 parts of A9 sodium feldspar, 6 parts of quartz powder, 6 parts of calcined kaolin, 15 parts of dolomite, 6 parts of burned talc, 3 parts of wollastonite, 6 parts of strontium carbonate, 1.5 parts of barium carbonate, 3.5 parts of zinc oxide, and 8 parts of ball clay. The chemical composition corresponding to the glaze includes: SiO2: 49.65%, Al2O3: 13.79%, MgO: 5.42%, CaO: 6.32%, Na2O: 4.86%, K2O: 0.29%, SrO: 4.17%, BaO: 1.18%, ZnO: 3.49%, ignition loss: 10.4%, and the remainder is impurities. The above-mentioned glaze raw materials are mixed with 0.15 parts of sodium carboxymethyl cellulose, 0.35 parts of sodium tripolyphosphate and 40 parts of water, and added into a ball mill for ball grinding until the particle size meets the requirements. The qualified particle size requirement is: at least 100mL of the material is pre-screened through a 100-mesh sieve, and then 100mL of the sieved liquid is screened through a 325-mesh sieve. The residue is dried and weighed to be 0.3g-0.5g; after the particle size meets the requirements, the ball is screened through a 120-mesh sieve to obtain the glaze, and then put into a slurry storage tank for use.
[0038] Among them, A9 sodium feldspar includes by mass percentage: SiO2: 72.30%, Al2O3: 16.63%, Fe2O3: 0.18%, TiO2: 0.03%, CaO: 0.57%, MgO: 0.36%, K2O: 0.39%, Na2O: 8.90%, ignition loss 0.65%; A10 sodium feldspar includes by mass percentage: SiO2: 72.78%, Al2O3: 16.65%, Fe2O3: 0.11%, Ti O2: 0.06%, CaO: 0.54%, MgO: 0.17%, K2O: 0.11%, Na2O: 9.23%, loss on ignition 0.36%; A11 albite includes, by mass percentage: SiO2: 73.18%, Al2O3: 16.46%, Fe2O3: 0.10%, TiO2: 0.07%, CaO: 0.55%, MgO: 0.17%, K2O: 0.18%, Na2O: 9.01%, loss on ignition 0.29%.
[0039] The raw materials of the green body layer include, by weight: 15 parts of white sand, 12 parts of ball clay, 4 parts of sodium stone powder, 29 parts of potassium sodium stone powder, 15 parts of kaolin, 5 parts of bentonite, 5 parts of talc particles, 2.0 parts of rotten brick particles, 6 parts of raw mud, and 7 parts of diopside. The raw materials of the green body layer are used as 100 parts of dry materials, and 0.54 parts of water glass, 0.68 parts of degumming agent J028 of Foshan Sanshui Taiyang New Materials Co., Ltd., 0.05 parts of sodium carboxymethyl cellulose and 40 parts of water are added to mix, put into a ball mill, and the ball milling is qualified when the residue passing through a 250-mesh sieve is 0.8%-1.2%. Then the slurry is discharged to remove iron and pass through an 80-mesh sieve to a slurry storage tank for aging for 24 hours. After aging and mixing, the slurry enters a spray tower for granulation. The granulated powder particles are transported to a powder silo for aging for 24 hours. The powder particles are transported to a press to be pressed into a green body. The green body enters a drying kiln at 180°C for 50 minutes. The green body layer is obtained when the green body comes out of the drying kiln.
[0040] The process of producing the diamond effect light-sensitive ceramic tile includes the following steps:
[0041] The body layer comes out of the drying kiln and enters the glaze line, and enters the water spray frame to spray 12 grams of water; after the body layer is sprayed with water, a bell cover is used to sprinkle the surface glaze, the surface glaze has a specific gravity of 1.89, the glaze amount is 65 grams, and the surface glaze is measured with a flow rate cup to be 45 seconds; after the body is sprinkled with the surface glaze, it enters the inkjet machine for inkjet printing, and while printing with inkjet printing, glue ink is printed on the designed pattern part, and then enters the automatic dry granulator to apply the combined dry granules. The dry granulator applies the combined dry granules to the printing glue ink position according to the grayscale of the glue channel, and then absorbs the combined dry granules that are not stuck to the brick surface through the particle suction nozzle; after applying the dry granules, the body enters the high-pressure gun to spray the polishing glaze, and the polishing glaze parameters are: glaze specific gravity 1.3, glaze amount 14 grams; after spraying the polishing glaze, a bell cover is used to sprinkle the polishing glaze, and the polishing glaze parameters are: glaze specific gravity 1.89, glaze amount 72 grams, and the polishing glaze is measured with a flow rate cup to be 45 seconds. After glazing, the tiles are fired in a kiln at a temperature of 1210°C for 45 minutes. After leaving the kiln, they are polished, waxed and edged to obtain finished tiles.
[0042] Among them, the glazing amount includes water application, and the glazing amount is measured based on a 400*400 mm plate.
[0043] The product photo of the diamond effect light-sensitive ceramic tile is as follows Figure 1 shown.
[0044] Example 2
[0045] A diamond effect light-sensitive ceramic tile, which is different from Example 1 in that:
[0046] (1) The ceramic dry particles include 2 parts of albite, 4 parts of dolomite, 17 parts of calcite, 13 parts of potassium carbonate, 6 parts of aluminum oxide, 46.5 parts of quartz powder, 1.5 parts of barium carbonate, and 10 parts of 99 zinc oxide by weight; 90 parts of the ceramic dry particles and 10 parts of zircon sand dry particles are mixed evenly to form a combined dry particle;
[0047] (2) The raw materials of the glaze include, by weight: 12 parts of nepheline powder, 6 parts of potassium feldspar, 12 parts of A11 sodium feldspar, 17 parts of A10 sodium feldspar, 14 parts of A9 sodium feldspar, 8 parts of quartz, 10.5 parts of high white alumina, 14 parts of calcined kaolin, 0.5 parts of dolomite, 1 part of calcined talc, and 5 parts of zirconium silicate;
[0048] (3) The raw materials for glazing include, by weight: 8 parts of A11 sodium feldspar, 13 parts of A10 sodium feldspar, 18 parts of A9 sodium feldspar, 4 parts of quartz powder, 4 parts of calcined kaolin, 17 parts of dolomite, 8 parts of burned talc, 3 parts of wollastonite, 8 parts of strontium carbonate, 3 parts of barium carbonate, 5.5 parts of zinc oxide, and 6.5 parts of ball clay.
[0049] The other parts and processes are the same as those in Example 1.
[0050] The product photo of the diamond effect light-sensitive ceramic tile is as follows Figure 2 shown.
[0051] Example 3
[0052] A diamond effect light-sensitive ceramic tile, which is different from Example 1 in that:
[0053] (1) The ceramic dry particles include 4 parts of albite, 1.5 parts of dolomite, 15 parts of calcite, 11 parts of potassium carbonate, 5 parts of aluminum oxide, 55 parts of quartz powder, 0.5 parts of barium carbonate, and 8 parts of 99% zinc oxide by weight; 50 parts of the ceramic dry particles and 50 parts of the zircon sand dry particles are mixed evenly to form the combined dry particles;
[0054] (2) The raw materials of the glaze include, by weight: 11 parts of nepheline powder, 10 parts of potassium feldspar, 8 parts of A11 sodium feldspar, 13 parts of A10 sodium feldspar, 10 parts of A9 sodium feldspar, 12 parts of quartz, 7 parts of high white alumina, 10 parts of calcined kaolin, 2 parts of dolomite, 5 parts of calcined talc, and 12 parts of zirconium silicate;
[0055] (3) The raw materials for glazing include, by weight: 12 parts of A11 sodium feldspar, 17 parts of A10 sodium feldspar, 24 parts of A9 sodium feldspar, 5 parts of quartz powder, 8 parts of calcined kaolin, 13 parts of dolomite, 4 parts of burned talc, 1 part of wollastonite, 4 parts of strontium carbonate, 0.5 parts of barium carbonate, 1.5 parts of zinc oxide, and 10 parts of ball clay.
[0056] The other parts and processes are the same as those in Example 1.
[0057] The product photo of the diamond effect light-sensitive ceramic tile is as follows Figure 3 shown.
[0058] Example 4
[0059] A diamond effect light-sensitive ceramic tile, which is different from Example 1 in that:
[0060] (1) The ceramic dry particles include 7 parts of albite, 1 part of dolomite, 21 parts of calcite, 9 parts of potassium carbonate, 10 parts of aluminum oxide, 45 parts of quartz powder, 1 part of barium carbonate, and 6 parts of 99% zinc oxide by weight; 80 parts of the ceramic dry particles and 20 parts of zircon sand dry particles are mixed evenly to form a combined dry particle;
[0061] (2) The raw materials of the glaze include, by weight: 8 parts of nepheline powder, 6 parts of potassium feldspar, 11 parts of A11 sodium feldspar, 16 parts of A10 sodium feldspar, 13 parts of A9 sodium feldspar, 8 parts of quartz, 11 parts of high white alumina, 14 parts of calcined kaolin, 1 part of dolomite, 3 parts of calcined talc, and 9 parts of zirconium silicate;
[0062] (3) The raw materials for glazing include, by weight: 9 parts of A11 sodium feldspar, 14 parts of A10 sodium feldspar, 20 parts of A9 sodium feldspar, 8 parts of quartz powder, 5 parts of calcined kaolin, 16 parts of dolomite, 5 parts of burned talc, 4 parts of wollastonite, 7 parts of strontium carbonate, 2 parts of barium carbonate, 4 parts of zinc oxide, and 6 parts of ball clay.
[0063] The other parts and processes are the same as those in Example 1.
[0064] The product photo of the diamond effect light-sensitive ceramic tile is as follows Figure 4 shown.
[0065] Example 5
[0066] A ceramic tile, which differs from Example 1 in that: the raw materials for glazing include, by weight: 6 parts of A11 sodium feldspar, 11 parts of A10 sodium feldspar, 16 parts of A9 sodium feldspar, 6 parts of quartz powder, 8 parts of calcined kaolin, 17 parts of dolomite, 8 parts of burned talc, 5 parts of wollastonite, 8 parts of strontium carbonate, 3 parts of barium carbonate, 5.5 parts of zinc oxide, and 6.5 parts of ball clay.
[0067] The other parts and processes are the same as those in Example 1.
[0068] Example 6
[0069] A ceramic tile, which differs from Example 1 in that: the raw materials for glazing include, by weight: 14 parts of A11 sodium feldspar, 19 parts of A10 sodium feldspar, 26 parts of A9 sodium feldspar, 5 parts of quartz powder, 4 parts of calcined kaolin, 13 parts of dolomite, 4 parts of burnt talc, 3 parts of wollastonite, 4 parts of strontium carbonate, 0.5 parts of barium carbonate, 1.5 parts of zinc oxide, and 6 parts of ball clay.
[0070] The other parts and processes are the same as those in Example 1.
[0071] Comparative Example 1
[0072] A ceramic tile, which is different from Example 1 in that the ceramic dry particles include 4 parts of albite, 2 parts of dolomite, 18 parts of calcite, 15 parts of potassium carbonate, 3 parts of aluminum oxide, 49 parts of quartz powder, 1 part of barium carbonate, and 8 parts of 99 zinc oxide by weight. The other parts and processes are the same as those in Example 1.
[0073] Comparative Example 2
[0074] A ceramic tile, which is different from Example 1 in that the ceramic dry particles include 2 parts of albite, 2 parts of dolomite, 18 parts of calcite, 8 parts of potassium carbonate, 12 parts of aluminum oxide, 49 parts of quartz powder, 1 part of barium carbonate, and 8 parts of 99 zinc oxide by weight. The other parts and processes are the same as those in Example 1.
[0075] Comparative Example 3
[0076] A ceramic tile, which is different from Example 1 in that 93 parts of ceramic dry particles and 7 parts of zircon sand dry particles are mixed as combined dry particles. Other parts and processes are the same as Example 1. Product photos are shown in the figure Figure 5 shown.
[0077] Comparative Example 4
[0078] A ceramic tile, which is different from Example 1 in that 45 parts of ceramic dry particles and 55 parts of zircon sand dry particles are mixed as combined dry particles. Other parts and processes are the same as Example 1. Product photos are shown in the figure Figure 6 shown.
[0079] The raw material composition and chemical composition of the ceramic dry particles in Examples 1 to 4 and Comparative Examples 1-2 are shown in Tables 1 and 2, respectively.
[0080] Table 1
[0081] Ceramic dry granule raw material ratio (parts) Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Sodium feldspar 4 2 4 7 4 2 dolomite 2 4 1.5 1 2 2 Calcite 18 17 15 21 18 18 Potassium carbonate 11 13 11 9 15 8 Alumina 7 6 5 10 3 12 Quartz powder 49 46.5 55 45 49 49 Barium carbonate 1 1.5 0.5 1 1 1 Zinc Oxide 8 10 8 6 8 8
[0082] Table 2
[0083] Chemical composition of ceramic dry particles (%) Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 <![CDATA[SiO2]]> 58.23 54.62 63.76 56.22 59.07 56.08 <![CDATA[Al2O3]]> 9.51 8.01 7.16 13.57 5.05 14.57 MgO 0.74 1.23 0.58 0.53 0.75 0.73 CaO 12.03 12.3 9.78 13.59 12.2 11.89 <![CDATA[Na2O]]> 0.49 0.25 0.48 0.86 0.50 0.24 <![CDATA[K2O]]> 8.66 10.35 8.51 7.14 11.94 6.27 BaO 0.88 1.34 0.43 0.89 0.90 0.87 ZnO 9.12 11.56 8.95 6.86 9.25 9.02 <![CDATA[Fe2O3]]> 0.08 0.07 0.08 0.08 0.08 0.07 <![CDATA[TiO2]]> 0.04 0.03 0.04 0.04 0.04 0.03 Burn reduction 0.17 0.18 0.15 0.19 0.17 0.17
[0084] The composition and chemical composition of the glaze in Examples 1 to 4 are shown in Tables 3 and 4, respectively.
[0085] Table 3
[0086]
[0087]
[0088] Table 4
[0089] Chemical composition of glaze (%) Example 1 Example 2 Example 3 Example 4 <![CDATA[SiO2]]> 56.82 56.39 57.48 56.40 <![CDATA[Al2O3]]> 25.59 29.33 22.21 28.62 MgO 1.35 0.58 2.24 1.35 CaO 1.24 1.22 1.59 1.17 <![CDATA[Na2O]]> 5.23 6.13 4.72 5.62 <![CDATA[K2O]]> 1.4 1.30 1.64 1.12 <![CDATA[Fe2O3]]> 0.19 0.21 0.18 0.21 <![CDATA[TiO2]]> 0.18 0.2 0.16 0.2 <![CDATA[ZrO2]]> 6.34 3.17 7.61 3.81 Burn reduction 1.42 1.29 1.92 1.31
[0090] The composition and chemical composition of the glazes in Examples 1 to 6 are shown in Tables 5 and 6, respectively.
[0091] Table 5
[0092] Glaze ratio (parts) Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 A11 Sodium Feldspar 10 8 12 9 6 14 A10 Sodium Feldspar 15 13 17 14 11 19 A9 Sodium Feldspar 20 18 24 20 16 26 Quartz powder 6 4 5 8 5 5 Calcined Kaolin 6 4 8 5 8 4 dolomite 15 17 13 16 17 13 Burnt Talc 6 8 4 5 8 4 Wollastonite 3 5 1 4 5 3 Strontium carbonate 6 8 4 7 8 4 Barium carbonate 1.5 3 0.5 2 4 0.5 Zinc Oxide 3.5 5.5 1.5 4 5.5 1.5 Ball Soil 8 6.5 10 6 6.5 6
[0093] Table 6
[0094] Chemical composition of glaze (%) Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 <![CDATA[SiO2]]> 49.65 43.97 54.03 48.45 44.05 54.68 <![CDATA[Al2O3]]> 13.79 11.35 16.73 12.41 11.95 14.99 MgO 5.42 6.54 4.31 5.31 6.54 4.33 CaO 6.32 7.67 4.99 6.98 7.65 5.72 <![CDATA[Na2O]]> 4.86 4.22 5.71 4.64 3.58 6.35 <![CDATA[K2O]]> 0.29 0.26 0.34 0.26 0.25 0.28 BaO 1.18 2.35 0.40 1.57 2.35 0.4 ZnO 3.49 5.48 1.50 3.99 5.48 1.5 <![CDATA[Fe2O3]]> 0.24 0.21 0.27 0.22 0.22 0.24 <![CDATA[TiO2]]> 0.15 0.13 0.19 0.14 0.14 0.17 SrO 4.17 5.56 2.78 4.86 5.65 2.78 Burn reduction 10.4 12.22 8.74 11.13 11.29 8.54
[0095] The ceramic tiles of Examples 1-6 and Comparative Examples 1-4 were tested. The test methods for wear resistance and antifouling performance were carried out according to the provisions of the ceramic tile testing standard GB / T4100-2015. The antifouling performance and glossiness were tested by sampling the area where the combined dry particles were relatively concentrated. The convex and concave feel of the glaze surface was determined by subjective touch of the area where the combined dry particles were concentrated and the contrast of the area with no or few combined dry particles. The transparency and dazzling diamond texture of the glaze surface were determined by subjective observation of the transparency of the glaze surface and the presentation of the dazzling diamond texture of the particles. The results are shown in Table 7.
[0096] Table 7
[0097]
[0098]
[0099] From the results of the examples, it can be seen that from Examples 1 to 4, it can be seen that the glaze of the ceramic tile can well present star-shaped bright spots at the position where the combined dry particles are designed. The touch of the dry particle gathering area and the position without or less combined dry particles are smooth and delicate. In Example 2, the ratio of ceramic dry particles to zircon sand dry particles is 9:1. The zircon sand dry particles are relatively few, and the brick glaze has a dazzling diamond effect, but the particle effect appears sparse. In Comparative Example 1, the aluminum oxide content is low, the potassium oxide content is high, and the firing temperature of the ceramic dry particles is low. During the firing process, the ceramic dry particles are easily eroded after high-temperature melting, which reduces the dazzling diamond effect on the brick surface. In Comparative Example 2, the aluminum oxide content is high, the potassium oxide content is low, and the temperature of the ceramic dry particles is high. Small protrusions are likely to appear at the position where the ceramic tile is designed with combined dry particles, and it is easy to be uneven during polishing. In Comparative Example 3, the ratio of zircon sand is reduced, and the ceramic tile glaze presents too few star-shaped bright spots at the position where the combined dry particles are designed, which is not obvious (as shown in the photo). Figure 5 As shown in the figure). In comparative example 4, the ratio of zircon sand was increased. In the position where the combined dry particles were designed, some zircon sand dry particles were stacked on the tile glaze surface. There were cavitations between the stacked particles, which affected the glaze effect of the tile. After some cavitations were polished and worn, the anti-fouling property and glossiness decreased (as shown in the photo). Figure 6As shown). Example 5, the glaze composition reduces the content of sodium feldspar. Sodium feldspar mainly introduces sodium oxide. The reduction of sodium oxide content will increase the firing temperature of the glaze, and the glass phase in the glaze is insufficient, and the glaze surface is not transparent. At the same time, it is easy to be not cooked at high temperature, resulting in a decrease in antifouling property. Example 6, the content of sodium feldspar is increased. Sodium feldspar mainly introduces sodium oxide. The increase of sodium oxide content increases the glass phase of the glaze, and the glaze surface has a strong sense of transparency, but the increase of glass phase weakens its wear resistance.
[0100] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.
Claims
1. A combined dry granule, characterized in that: The invention comprises ceramic dry particles and zircon sand dry particles; the raw materials for preparing the ceramic dry particles comprise, by weight, 2-7 parts of albite, 1-4 parts of dolomite, 15-21 parts of calcite, 9-13 parts of potassium carbonate, 5-10 parts of aluminum oxide, 45-55 parts of quartz powder, 0.5-1.5 parts of barium carbonate and 6-10 parts of zinc oxide; the zircon sand dry particles are obtained by crushing zircon; the mass ratio of the ceramic dry particles to the zircon sand dry particles is (5-9):(1-5).
2. The combined dry granules according to claim 1, characterized in that: The particle size distribution of the zircon sand dry particles is: 70 meshes-140 meshes≥75%, 140 meshes-200 meshes≤23%, below 200 meshes≤1.8%, and above 70 meshes≤0.2%.
3. The combined dry granules according to claim 2, characterized in that: The particle size distribution of the ceramic dry particles is the same as the particle size distribution of the zircon sand dry particles.
4. A method for preparing the combined dry particles according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing the ceramic dry particles with the zircon sand dry particles to obtain the combined dry particles; and the preparation process of the ceramic dry particles comprises the following steps: mixing the raw materials, melting them, quenching them with water to form frit particles, drying them, and crushing them.
5. The preparation method according to claim 4, characterized in that: The melting temperature is 1530° C.-1570° C.; and / or, dried to a moisture content of less than 0.05%.
6. A diamond effect light-sensitive ceramic tile, characterized in that: The invention comprises, from bottom to top, a body layer, a glaze layer, a printing layer, a glue dry particle layer, and a glaze polishing layer; the glue dry particle layer comprises the combined dry particles according to any one of claims 1 to 3.
7. The diamond effect light-sensitive ceramic tile according to claim 6, characterized in that: The surface glaze layer is formed by a surface glaze, and the surface glaze comprises, by weight: 8-12 parts of nepheline powder, 6-10 parts of potassium feldspar, 8-12 parts of A11 sodium feldspar, 13-17 parts of A10 sodium feldspar, 10-14 parts of A9 sodium feldspar, 8-12 parts of quartz, 7-11 parts of high white alumina, 10-14 parts of calcined kaolin, 0.5-2 parts of dolomite, 1-5 parts of burned talc, and 5-12 parts of zirconium silicate; The A9 albite comprises, by mass percentage, SiO2: 72.30%, Al2O3: 16.63%, Fe2O3: 0.18%, TiO2: 0.03%, CaO: 0.57%, MgO: 0.36%, K2O: 0.39%, Na2O: 8.90%, and ignition loss 0.65%; The A10 sodium feldspar comprises, by mass percentage, SiO2: 72.78%, Al2O3: 16.65%, Fe2O3: 0.11%, TiO2: 0.06%, CaO: 0.54%, MgO: 0.17%, K2O: 0.11%, Na2O: 9.23%, and ignition loss: 0.36%; The A11 sodium feldspar comprises, by mass percentage, SiO2: 73.18%, Al2O3: 16.46%, Fe2O3: 0.10%, TiO2: 0.07%, CaO: 0.55%, MgO: 0.17%, K2O: 0.18%, Na2O: 9.01%, and loss on ignition 0.29%.
8. The diamond effect light-sensitive ceramic tile according to claim 6, characterized in that: The polishing glaze layer is formed by polishing glaze, and the polishing glaze includes, by weight: 8-12 parts of A11 sodium feldspar, 13-17 parts of A10 sodium feldspar, 18-24 parts of A9 sodium feldspar, 4-8 parts of quartz powder, 4-8 parts of calcined kaolin, 13-17 parts of dolomite, 4-8 parts of burned talc, 1-5 parts of wollastonite, 4-8 parts of strontium carbonate, 0.5-3 parts of barium carbonate, 1.5-5.5 parts of zinc oxide, and 6-10 parts of ball clay; The A9 albite comprises, by mass percentage, SiO2: 72.30%, Al2O3: 16.63%, Fe2O3: 0.18%, TiO2: 0.03%, CaO: 0.57%, MgO: 0.36%, K2O: 0.39%, Na2O: 8.90%, and ignition loss 0.65%; The A10 sodium feldspar comprises, by mass percentage, SiO2: 72.78%, Al2O3: 16.65%, Fe2O3: 0.11%, TiO2: 0.06%, CaO: 0.54%, MgO: 0.17%, K2O: 0.11%, Na2O: 9.23%, and ignition loss: 0.36%; The A11 sodium feldspar comprises, by mass percentage, SiO2: 73.18%, Al2O3: 16.46%, Fe2O3: 0.10%, TiO2: 0.07%, CaO: 0.55%, MgO: 0.17%, K2O: 0.18%, Na2O: 9.01%, and loss on ignition 0.29%.
9. A method for preparing the dazzling diamond effect light-sensitive ceramic tile according to any one of claims 6 to 8, characterized in that: The following steps are involved: A surface glaze is applied on the green body layer to form the surface glaze layer, and then inkjet printing is performed to form a printing layer, and colloidal ink is printed on the pattern of the printing layer, and then the combined dry particles are applied, and the unadhered combined dry particles are removed, and then a polishing glaze is applied to form the polishing glaze layer, and the polishing glaze layer is fired to obtain the dazzling diamond effect light-sensitive ceramic tile.
10. The preparation method according to claim 9, characterized in that: The firing temperature is 1200° C.-1220° C., and the firing time is 30 min-60 min; and / or, after the firing is completed, the ceramic tile is polished, waxed, and edged to obtain the diamond effect ceramic tile.
Citation Information
Patent Citations
Diamond dry particles, glazed brick with positioning diamond flashing effect and preparation method of glazed brick
CN111423113A
Glittery cover glaze and preparation method thereof, and preparation method of ceramic tile with glittery effect
CN112707642A
Preparation process of glazed tile capable of forming plaque-shaped random crystallization effect and product thereof
CN113248286A
Marble-imitated ceramic tile with fantasy-color flashing dry particles and positioning diamond fantasy-color effect
CN115043589A
Colored flash dry particles, colored dazzle light ceramic tile and preparation method of colored flash dry particles and colored dazzle light ceramic tile
CN118545909A
Cited By
Preparation method of combined dry particle cluster, ceramic rock plate with different-color and special-shaped pattern decoration effect and preparation method of ceramic rock plate
CN120841840A
Combined ice crystal dry particle multi-dimensional light-sensitive starry sky stone and preparation method thereof
CN121517240A